Tribological behaviour of sintered iron based self-lubricating composites - Jose Daniel Biasoli De Mello; Cristiano Binder; Gisele Hammes; Roberto Binder; Aloisio Nelmo Klein (Friction)
Abstract This work is a review of previous works, presenting and discussing the most important results obtained by an ongoing research program towards the development of innovative, low-cost, self-lubricating composites with a low friction coefficient and high mechanical strength and wear resistance. Special emphasis is given to uniaxial die pressing of solid lubricant particles mixed with matrix powders and to metal injection moulding associated with in situ generation of solid lubricant particles. Initially, a microstructural model/processing route (powder injection moulding followed by plasma-assisted debinding and sintering) produced a homogeneous dispersion of in situ generated solid lubricant particles. Micrometric nodules of graphite with diameter smaller than 20 μm were formed, constituting a nanostructured stacking of graphite foils with nanometric thickness. Micro Raman analysis indicated that the graphite nodules were composed of turbostratic 2D graphite having highly misaligned graphene planes separated by large interlamellae distance. Large interplanar distance between the graphene foils and misalignment of these foils were confirmed by transmission electron microscopy and were, probably, the origin of the outstandingly low dry friction coefficient (0.04). The effect of sintering temperature, precursor content, metallic matrix composition and surface finish is also reported. Furthermore, the influence of a double-pressing/double-sintering (DPDS) technique on the tribological performance of self-lubricating uniaxially die-pressed hBN + graphite-Fe-Si-C-Mo composite is also investigated. Moreover, the tribological behaviour of die-pressed Fe-Si-C matrix composites containing 5, 7.5 and 10 wt% solid lubricants (hBN and graphite) added during the mixing step is analysed in terms of mechanical properties and wear mechanisms. Finally, the synergy between solid lubricant particles dispersed in a metallic matrix and fluid lubricants in a cooperative mixed lubrication regime is presented.